Lymphoid tissue fibrosis is associated with impaired vaccine responses - Kityo, Cissy; Makamdop, Krystelle Nganou; Rothenberger, Meghan; Chipman, Jeffrey G.; Hoskuldsson, Torfi; Beilman, Gregory J.; Grzywacz, Bartosz; Mugyenyi, Peter; Ssali, Francis; Akondy, Rama S.; Anderson, Jodi; Schmidt, Thomas E.; et al. (Journal of Clinical Investigation, 2018)
Vaccine responses vary by geographic location. We have previously described how HIV-associated inflammation leads to fibrosis of secondary lymph nodes (LNs) and T cell depletion. We hypothesized that other infections may cause LN inflammation and fibrosis, in a process similar to that seen in HIV infection, which may lead to T cell depletion and affect vaccine responses. We studied LNs of individuals from Kampala, Uganda, before and after yellow fever vaccination (YFV) and found fibrosis in LNs that was similar to that seen in HIV infection. We found blunted antibody responses to YFV that correlated to the amount of LN fibrosis and loss of T cells, including T follicular helper cells. These data suggest that LN fibrosis is not limited to HIV infection and may be associated with impaired immunologic responses to vaccines. This may have an impact on vaccine development, especially for infectious diseases prevalent in the developing world.
CRIS-Team Scopus Importer:2024-09-09